Engaging healthcare students in innovative approaches for antimicrobial resistance containment - Kasujja, Hassan; Kajumbula, Henry; Tusiimire, Jonans; Waswa, J.P.; Nanyonga, Stella M.; Kiggundu, Reuben; Mwandah, Daniel C.; Murungi, Marion; Mugenyi, Nathan; Mukenya, Irene M.; Joshi, Mohan P.; Schwarz, Dan; et al. (Journal of Public Health in Africa, 2024)
Antimicrobial resistance (AMR) occurs when organisms change over time and no longer respond to medicines making infections harder to treat.1 Antimicrobial resistance continues to impact global populations, increasing morbidity and mortality, straining healthcare systems and reducing countries’ gross domestic product.2,3 It is a leading cause of death worldwide, with an estimated 4.5 million associated deaths, which is expected to grow to 10 million deaths per year by 2050 if not responded to adequately.3 Furthermore, it is estimated that without adequate action, AMR could lead to a global reduction in gross domestic product of $3.4 trillion annually by 2030.4 For this reason, combating AMR is among the action packages of the Global Health Security Agenda.5 Although inappropriate use of antimicrobials is the leading driver of AMR, which is most evident in low-income countries, other factors, such as poor infection prevention and control and insufficient practices in water, sanitation and hygiene, contribute to the problem.6,7 According to the 2022 World Health Organization (WHO) Global AMR and Use Surveillance System report, Uganda had one of the highest antimicrobial consumption rates, with a defined daily dose of nearly 60 per 1000.8 Among the key drivers of inappropriate antimicrobial use and poor infection prevention and control practices are inadequate knowledge and incorrect attitude among healthcare workers.9,10 Various studies worldwide have identified significant gaps in the AMR component in pre-service and in-service curricula for health professionals.9,11,12,13 A survey conducted between 2018 and 2019 using self-administered questionnaires found that only 36.6% of final-year medical and pharmacy students from three universities in Uganda, Kenya and Tanzania were adequately trained about AMR and antibiotic use in clinical scenarios.14 As a strategy for strengthening human resource capacity for AMR containment, the WHO Global Action Plan on AMR recommends integrating AMR into professional education, training and certification of the One Health workforce.15 To guide this process, WHO developed a competency framework for health workers’ education and training on AMR.16 A recent analysis of Uganda’s school educational curricula revealed a significant deficiency in basic AMR principles and health security across all education levels. Students under 16 years receive less than 40% of the necessary content. There is a complete absence of content on rational antibiotic use, health-seeking behaviours and One Health, highlighting the need to incorporate additional AMR content and undertake policy reviews to address these gaps.
Keywords: Antimicrobial resistance (AMR); Healthcare students; Treatment; Population health